Catalytic oxidation of aromatic compounds by nanostructured ruthenium dioxide - Lepikh, Ya.I.; Doycho, I.K. (Physics and Chemistry of Solid State, 2023)
Physico-chemical processes that can be used to free industrial leaks from contamination with aromatic compounds were considered in this work. It has been demonstrated that catalytic oxidation with ruthenium dioxide can serve as an effective purification method. An original way of detection of the catalytic oxidation process completion by the photoluminescent method is proposed. A block diagram of the purification setup is given. The results can be used to solve the problem of protecting the environment from certain harmful pollutants.